Intercellular Communication in Tumor Biology: A Role for Mitochondrial Transfer - Herst, Patries M.; Dawson, Rebecca H.; Berridge, Michael V. (Frontiers in Oncology, 2018)
The current view that mitochondria are essential semi-autonomous, cell-constrained organelles that communicate with the nucleus in real time to regulate cell metabolism is challenged by an increasing body of evidence that points to their intercellular mobility. Both cell co-culture approaches and more recently, in vivo experiments demonstrate that mitochondria not only can, but do move between cells, most commonly from donor cells to recipient cells with compromised mitochondrial respiration. Compromised mitochondrial respiration can result from mutations in mitochondrial or nuclear DNA that affect functionality of the respiratory chain. Intercellular mitochondrial transfer occurring as a consequence of radiation or chemotherapy can, potentially lead to treatment resistance. In tumour biology, tissue stromal cells have been shown to efficiently transfer functional mitochondria to tumour cells without mitochondrial DNA, restoring their capacity for respiration, metabolic function and adaptability to ongoing changes in the tumour microenvironment. Mechanisms of intercellular mitochondrial transfer differ between different tissues and cell types and include long-distance membrane nanotubes, direct cell to cell contact and extracellular vesicles. Both short-term tissue maintenance and long-term mitochondrial replacement have been demonstrated, raising the possibility of therapeutically manipulating mitochondrial transfer in cancer treatment.